Survivorship after childhood cancer: PanCare: A European Network to promote optimal long-term care. Issue 10 (July 2015) - Hjorth, Lars; Haupt, Riccardo; Skinner, Roderick; Grabow, Desiree; Byrne, Julianne; Karner, Sabine; Levitt, Gill; Michel, Gisela; van der Pal, Helena; Bárdi, Edit; Beck, Jörn D.; de Vathaire, Florent; et al.
Abstract Survival after childhood cancer has improved substantially over recent decades. Although cancer in childhood is rare increasingly effective treatments have led to a growing number of long-term survivors. It is estimated that there are between 300, 000 and 500, 000 childhood cancer survivors in Europe. Such good survival prospects raise important questions relating to late effects of treatment for cancer. Research has shown that the majority will suffer adverse health outcomes and premature mortality compared with the general population. While chronic health conditions are common among childhood cancer survivors, each specific type of late effect is very rare. Long-term effects must be considered particularly when addressing complex multimodality treatments, and taking into account the interaction between aspects of treatment and genotype. The PanCare Network was set up across Europe in order to effectively answer many of these questions and thereby improve the care and quality of life of survivors. The need for a structured long-term follow-up system after childhood cancer has been recognised for some time and strategies for implementation have been developed, first nationally and then trans-nationally, across Europe. Since its first meeting in Lund in 2008, the goal of the PanCare Network has been to coordinate and implement these strategies to ensure that every European survivor of childhood and adolescent cancer receives optimal long‐term care. This paper will outline the structure and work of the PanCare Network, including the results of several European surveys, the start of two EU-funded projects and interactions with relevant stakeholders and related projects.